Academic performance of pediatric epileptic patients at King Abdulaziz University Hospital - Osama Y. Muthaffar; Hadeel Bakheet; Abdulaziz AlKhoshi; Maha Alsaiari; Saher Algarni; Abdulaziz Shaheen; Abdullah Zuhairy (Journal of Family Medicine and Primary Care)
Background: Epilepsy is a prevalent neurological condition affecting children worldwide, with a particularly high incidence in Saudi Arabia. Children with epilepsy can experience poor school performance due to cognitive deficits and frequent absences. This study investigates the impact of seizures on school attendance among children with epilepsy. Methods: This cross-sectional study was conducted at King Abdulaziz University Hospital (KAUH) in Jeddah, Saudi Arabia, including pediatric epilepsy patients from 2016 to 2022. Data were collected via an online questionnaire and analyzed using IBM SPSS. Factors examined included seizure frequency, medication use, comorbidities, teacher awareness, and absenteeism. Results: The study included 207 pediatric epilepsy patients, predominantly Saudi nationals (87%). Most parents had higher education backgrounds (70%). Participants’ mean age was 9.66 years, with 57% diagnosed before the age of 5. Most (45%) patients took daily medication with 57% experiencing no side effects. Over half (56%) of the population reported focus and memory problems, significantly related to age at diagnosis (P < 0.001). Comorbidities were reported by 35%, with a significant relationship to absenteeism (P < 0.01). Teacher awareness was reported in 58% of cases. Regarding absenteeism, over half (57%) were absent fewer than 10 days during the past academic year, with 41% attributing absenteeism to non-seizure reasons. Seizure attacks at home caused 22% of absences. A significant relationship existed between the etiology of absenteeism and seizures (P < 0.001). Bullying at school due to seizures was reported, with a significant relationship to absenteeism (P = 0.02). Conclusion: This study highlights the complex relationship between epilepsy, school attendance, and associated factors among pediatric patients in Saudi Arabia, shedding light on the importance of poor academic experience to improve the quality of life for children with epilepsy.